Effect of protease on apparent crude protein and metabolisable energy digestibilities in broiler chickens fed low protein diet - Law, Elizabeth Fang Lin; Idrus, Zulkifli; Soleimani Farjam, Abdoreza (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
A study was conducted to determine the effects of two types of commercial protease on apparent crude protein and metabolisable energy digestibilities of 27 day-old boiler chickens. Apparent crude protein (ACP) and metabolisable energy (AME) were reduced in low protein diet (CP16). Protease B significantly increased ACP and AME digestibility.